Mid-Holocene East Asian summer monsoon and vegetation changes recorded by a stalagmite from Huangjin Cave, northern China - Bin Zhao; Yongjin Wang; Liang Ning; Qingfeng Shao; R. Lawrence Edwards; Yijia Liang; Kan Zhao (Quaternary Science Reviews, 2026)

Millennial-to multi-centennial-scale Asian summer monsoon variability during Termination I: Evidence from stalagmite δ18O in Wanxiang Cave, northwestern China - Hongyu Shi; Pingzhong Zhang; Xianfeng Wang; Shaoneng He; Shufang Yuan; Ruitao Deng; Wei Jia; Shuyu Xue; Hai Cheng; R. Lawrence Edwards (Quaternary Science Reviews, 2026)

A submerged speleothem record from Cozumel Island: insights into Mexican Caribbean climate variability during the last deglaciation - Daisy Valera-Fernández; Rafael López-Martínez; Fernando Gázquez; Miguel Bartolomé; Ana Moreno; Eneko Iriarte; Juan Luis Bernal-Wormull; Lawrence Edwards; Hai Cheng; Elizabeth Solleiro-Rebolledo; Juan Pablo Bernal-Uruchurtu; Liliana Corona-Martínez; et al. (Quaternary Science Reviews, 2026)

Late Holocene hydroclimate changes in central China: Evidence from a multi-proxy stalagmite from Xiniu Cave - Tanui Moses Kipkorir; Kui Gao; Qihang Zhang; Kan Zhao; Zhigang Zhang; Xiuyang Jiang; Yue Li; Jingwei Zhang; Yongjin Wang; R. Lawrence Edwards; Xinggong Kong (Quaternary Science Reviews, 2026)

Reconstructing historical extreme precipitation from an aragonite-calcite stalagmite using trace-element ratios - Jiayu Lu; Haiwei Zhang; Hanying Li; Xinnan Zhao; Rui Zhang; Lijuan Sha; Jian Wang; Xiyu Dong; R. Lawrence Edwards; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Climate sensitivity and glacial inception in the European Alps across marine isotope stage 11 and 10 - Alexandre Honiat; Jonathan L. Baker; Gina E. Moseley; Martin Trüssel; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Continuous speleothem record from central Tunisia (the Mine cave) reveals climatic events for the last 27 ka - Sahar Ben Hamida; Chedia Zaara Ben Mosbah; Walid Oueslati; Dominique Blamart; Hai Cheng; R. Lawrence Edwards; Matthieu Fournier; Dominique Genty (Quaternary Science Reviews, 2026)

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Timing and amplitude of hydroclimate changes during the last glacial cycle in southwestern North America - Simon D. Steidle; Yuri Dublyansky; Marco Roman; Gina E. Moseley; Kathleen A. Wendt; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Millennial-scale hydroclimate variability of the Asian monsoon during MIS 9 from stalagmite records - Sinan Wang; Xunlin Yang; Hai Cheng; Wenming Zhou; Guofeng Li; Wanli Xiang; Rui Zhang; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Hydroclimate changes on the Chinese loess plateau during Marine isotope stage 3 revealed by multi-proxy speleothem records - Yijia Liang; Bin Zhao; Jinguo Dong; Jiaqi Cong; Peng Zhang; Yongjin Wang; R. Lawrence Edwards (Quaternary Science Reviews, 2026)

Perinatal environmental exposures, maternal mental health and cognitive outcomes in very preterm infants born in urban London - Zeyuan Sun; Kaili Liang; Andrew Lawrence; Marguerite Leoni; Serena J. Counsell; Paola Dazzan; A David Edwards; Chiara Nosarti (International Journal of Hygiene and Environmental Health, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Speleothem-based reconstruction of Holocene changes in monsoonal patterns and environmental conditions in Central Brazil - Marcela Eduarda Della Libera; Julio Cauhy; Cintia Stumpf; Roberto V. Santos; Francisco W. Cruz; Nicolas M. Stríkis; Luciana F. Prado; Jean-Sebastian Moquet; Michael Weber; Rebecca Orrison; Hai Cheng; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Disentangling ENSO- and ITCZ-related hydroclimate signals from replicated stalagmite multiproxy over the past 2500 years - Kui Gao; Tanui Moses Kipkorir; Kan Zhao; Xiuyang Jiang; Jingwei Zhang; Qihang Zhang; Junji Zhu; Sixian Wang; Yongjin Wang; Zhenqiu Zhang; Qingfeng Shao; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Detailed Asian summer monsoon changes during the Mid Holocene and their teleconnections with the northern high latitudes - Bin Zhao; Yingfang Cui; Kan Zhao; Yongjin Wang; Hai Cheng; R. Lawrence Edwards; Yijia Liang (Quaternary Science Reviews, 2025)

Monsoonal and westerly influences on interglacial calcite deposition and environmental conditions in southern Tibetan Plateau - Haibo Wang; Carlos Pérez-Mejías; Xianyan Wang; Tingyong Li; Can Yang; Hanying Li; Shihao Lei; Youfeng Ning; R. Lawrence Edwards; Hai Cheng (Quaternary Science Reviews, 2025)

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Exposure and Risk of Toxic Elements through Medicinal Hydrophytes - Kofi Sarpong; Edward Ankapong; Opoku Gyamfi; Jemima Tiwaa Marfo; Lawrence Brenyah-Kankam; Victor Agyei; Godfred Darko (Biological Trace Element Research, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

17Oexcess in Devils Hole calcite: an indicator of equilibrium fractionation and paleo moisture sources - Hagit P. Affek; Eugeni Barkan; Yael Tal; Simon D. Steidle; Kathleen A. Wendt; Christoph Spötl; R. Lawrence Edwards; Ekaterina Fishman; Yuri Dublyansky (Earth and Planetary Science Letters, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Societal responses to cold-season rainfall variability: a speleothem perspective on Byzantine and Hittite climate interactions in Late Holocene Türkiye and southeast Europe - Alistair W. Morgan; Alice R. Paine; Koray Koç; John Haldon; Elisa Hofmeister; Hai Cheng; Okan Tüysüz; Albert Matter; Lawrence R. Edwards; Negar Haghipour; Irka Hajdas; Dominik Fleitmann (Quaternary Science Reviews, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Hydroclimate variability in southwest China during Marine Isotope Stage 9: Insights from multi–proxy stalagmite records - Wei Jia; Yan Yang; Hai Cheng; Tingyong Li; Jingyao Zhao; Shaoneng He; Guangxin Liu; Xiao Liu; Lidan Lei; Mingyang Li; R. Lawrence Edwards (Quaternary Science Reviews, 2025)

Rapid Indian Monsoon response to the Younger Dryas event in the Southeastern Tibetan Plateau - Xiqian Wang; Liangcheng Tan; Ashish Sinha; Hai Xu; Haiwei Zhang; Jianghu Lan; Jin Zhang; Tianli Wang; Dong Li; Le Ma; Jingjie Zang; Xing Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum to “Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite” [Marine Geology 471 (2024) 107289] - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2025)

Routine large-scale movements of the yelloweye rockfish (Sebastes ruberrimus) - Leif K. Rasmuson; Matthew T. O. Blume; Kelly A. Lawrence; Bruce M. Laughlin; Christopher A. Edwards; Mark R. Terwilliger; A. Camille Ayrea; Alexandra G. McInturf; Bryan J. Legare; Taylor K. Chapple (Frontiers in Marine Science, 2025)
Of the seven species of Pacific rockfish declared overfished in the California Current in 2008, yelloweye rockfish ( Sebastes ruberrimus ) is the only remaining overfished rockfish species. Part of the original rebuilding plan included designation of a yelloweye rockfish conservation area, a rocky reef closed off the Central Coast of Oregon that is closed to bottom fishing. The yelloweye rockfish conservation area’s ability to help rebuild the population, is predicated on the theory that demersal rockfishes are relatively sedentary. However, in the years since being declared overfished, acoustic tagging studies suggested yelloweye rockfish did not remain in the yelloweye rockfish conservation area. However, where they went remained a mystery. In this paper we describe the use of pop-off satellite tags to conduct a mark-recapture study of 11 yelloweye rockfish tagged within the Stonewall Bank Yelloweye Rockfish Conservation Area. We used back-in-time particle tracking coupled with an ocean circulation model in an attempt to increase the precision in the location at which each tag shed off the fish, and further validated that location by associating it to the underlying seafloor habitat type. Ten out of eleven tags were shed from the fish while it was outside the Stonewall Bank Yelloweye Rockfish Conservation Area’s boundary. While most fish remained within 50 km of the Stonewall Bank Yelloweye Rockfish Conservation Area, one tagged fish swam to an offshore reef off Central Washington (~40 km from the shore). Backtracked locations were more likely over rock than the initial satellite transmission, indicating the method was effective at identifying tag shed locations. We found no relationship between days at large, fish sex or length and the distance between release site and shed location. Our work supports a growing body of work that suggests yelloweye rockfish have less site fidelity than previously hypothesized.

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Climate controls on speleothem initial 234U/238U ratios in midlatitude settings over two glacial cycles - Carlos Pérez-Mejías; Jian Wang; Youfeng Ning; Ana Moreno; Antonio Delgado-Huertas; R. Lawrence Edwards; Hai Cheng; Heather M. Stoll (Geochimica et Cosmochimica Acta, 2025)

Tufas record significant imprints of climate and tectonic activity over the past 600 ka: Evidence from a multi-story wedge in Northwest Africa - Khalil Azennoud; Yassine Ait Brahim; Abdennasser Baali; Franziska A. Lechleitner; Hicham El Asmi; Xianglei Li; R. Lawrence Edwards; Matthew Peros (Sedimentary Geology, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Multicentennial-scale coupling of the East Asian monsoon to North Atlantic climates during the Last Glacial Maximum - Yingfang Cui; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Quan Wang; Zhenjun Wang; Jianshun Chen; Hai Cheng; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Antileishmanial natural products as potential inhibitors of the Leishmania pteridine reductase: insights from molecular docking and molecular dynamics simulations - Abigail Kusiwaa Adomako; Edward Ntim Gasu; Jehoshaphat Oppong Mensah; Lawrence Sheringham Borquaye (In Silico Pharmacology, 2024)

Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Evaluation of four human-associated fecal biomarkers in wastewater in Southern Ontario - Charles Chettleburgh; Sean Xiao Ma; Megan Swinwood-Sky; Hanlan McDougall; Devita Kireina; Gurleen Taggar; Edward McBean; Valeria Parreira; Lawrence Goodridge; Marc Habash (Science of The Total Environment, 2023)

The control of particulate matter and hydrogeochemistry on uranium–thorium partition coefficients in two representative lakes, Qaidam Basin, China - Pu Zhang; Zhe Zhang; Lei Li; Chenyang Cao; Xuerou Li; Guangyou Zhu; R. Lawrence Edwards (Sedimentary Geology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Millennial-scale changes in the Asian monsoon during the MIS12 period as recorded by a Chinese stalagmite - Shaohua Yang; Shitao Chen; Yongjin Wang; Qingfeng Shao; Liangcheng Tan; Zhenqiu Zhang; Kan Zhao; Zhenjun Wang; Yijia Liang; Xiumin Zhai; Chuan-Chou Shen; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The spatio-temporal pattern of Asian summer monsoon during glacial Termination II recorded by Chinese stalagmite δ18O - Wei Jia; Pingzhong Zhang; Xianfeng Wang; Shaoneng He; Guangxin Liu; Hongyu Shi; Binggui Cai; Shufang Yuan; Wenfei Zhang; Ruitao Deng; Leilei Zhang; Tao Gao; et al. (Quaternary Science Reviews, 2023)

Long-term trends in nitrate and chloride in streams in an exurban watershed - Emma S. Castiblanco; Peter M. Groffman; Jonathan Duncan; Lawrence E. Band; Edward Doheny; Gary T. Fisher; Emma Rosi; Amanda K. Suchy (Urban Ecosystems, 2023)

Climatic stability recorded in speleothems may contribute to higher biodiversity in the Cape Floristic Region - Kerstin Braun; Richard M. Cowling; Miryam Bar‐Matthews; Alan Matthews; Avner Ayalon; Tami Zilberman; Mark Difford; R. Lawrence Edwards; Xianglei Li; Curtis W. Marean (Journal of Biogeography, 2023)
Aim The geography and genesis of diversity remain an enduring topic in ecology and evolution. Mediterranean Climate Ecosystems (MCEs), with their high plant diversities in winter rainfall climates, pose a challenge to popular hypotheses evoking high water availability and temperature as necessary for the evolution of high diversity. We test the hypothesis of environmental stability as a driver for the evolution of regional‐scale floristic diversity using speleothem oxygen (δ 18 O) and carbon (δ 13 C) isotopic values as proxies for past climatic variability in the Cape Floristic Region (CFR) and other MCEs. Location south‐western Africa, California, Mediterranean Basin. Taxon Plantae. Methods We present new speleothem δ 18 O and δ 13 C records from a cave near Robertson in the western CFR. Stable isotope samples included in the analyses cover the time intervals between 240 and 670 ka BP with hiatuses at 630–500 ka and 360–310 ka. The dispersion of these stable isotope records is used as a measure for climatic variability. We compare our new analyses to speleothem records that cover full glacial and interglacial conditions in other MCEs (California and the Mediterranean Basin) as well as in eastern regions of the CFR. All sites used in this comparison have lower vascular plant biodiversity than the western CFR. Results Analyses of the dispersion of the δ 18 O and δ 13 C datasets suggest that the highly diverse western CFR experienced climatic stability across several glacial–interglacial cycles, compared with the less diverse regions within and outside of the CFR. Main Conclusion This result provides support for the hypothesis that lower extinction rates associated with Pleistocene biome stability may explain the higher diversity in the CFR relative to other MCEs.

Investigating spatio-temporal variability of initial 230Th/232Th in intertidal corals - Hong-Wei Chiang; Belle Philibosian; Aron J. Meltzner; Chung-Che Wu; Chuan-Chou Shen; R. Lawrence Edwards; Chih-Kai Chuang; Bambang W. Suwargadi; Danny H. Natawidjaja (Quaternary Science Reviews, 2023)

An annually laminated stalagmite from the eastern Qinghai-Tibetan Plateau provides evidence of climate instability during the early MIS5e in the Asian summer monsoon - Tao Gao; Pingzhong Zhang; Hai Cheng; Leilei Zhang; Xinhu Li; Hongyu Shi; Wei Jia; Youfeng Ning; Hanying Li; R. Lawrence Edwards (Science China Earth Sciences, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Simulating the Impacts of an Applied Dynamic Adaptive Pathways Plan Using an Agent-Based Model: A Tauranga City, New Zealand, Case Study - Andrew Allison; Scott Stephens; Paula Blackett; Judy Lawrence; Mark Edward Dickson; Yvonne Matthews (Journal of Marine Science and Engineering, 2023)
Climate change and relative sea-level rise (RSLR) will increasingly expose coastal cities to coastal flooding, erosion, pluvial and fluvial flooding, episodic storm-tide flooding and eventually, permanent inundation. Tools are needed to support adaptive management approaches that allow society to adapt incrementally by making decisions now without creating path dependency and compromising decision-making options in the future. We developed an agent-based model that integrates climate-related physical hazard drivers and socio-economic drivers. We used it to explore how adaptive actions might be sequentially triggered within a low-elevation coastal city in New Zealand, in response to various climate change and socio-economic scenarios. We found that different adaptive actions are triggered at about the same RSLR level regardless of shared socio-economic pathway/representative concentration pathway scenario. The timing of actions within each pathway is dictated mainly by the rate of RSLR and the timing and severity of storm events. For the representative study site, the model suggests that the limits for soft and hard protection will occur around 30 cm RSLR, fully-pumped water systems are viable to around 35 cm RSLR and infrastructure upgrades and policy mechanisms are feasible until between 40 cm and 75 cm RSLR. After 75 cm RSLR, active retreat is the only remaining adaptation pathway.

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

The structure of marine isotope Stage 11 and its alignment with the Holocene - Yong Wang; Xunlin Yang; Yongjin Wang; Quan Wang; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Observing Extreme Ocean and Weather Events Using Innovative Saildrone Uncrewed Surface Vehicles - Dongxiao Zhang; Andy Chiodi; Chidong Zhang; Gregory Foltz; Meghan Cronin; Calvin Mordy; Jessica Cross; Edward Cokelet; Jun Zhang; Chris Meinig; Noah Lawrence-Slavas; Phyllis Stabeno (Oceanography, 2023)
Extreme ocean events and severe weather systems have large environmental impacts but are under-observed due to their harsh conditions and associated challenges with deployments of in situ observing platforms. Through a public-private partnership, the NOAA Pacific Marine Environmental Laboratory (PMEL) has developed the Saildrone uncrewed surface vehicle (USV) into a viable air-sea interaction observing platform that can be utilized by the broader ocean research community. PMEL and the NOAA Atlantic Oceanographic and Meteorological Laboratory (AOML) have demonstrated the potential of USVs for observing the Arctic marginal ice zone during the seasonal Arctic ice retreat and for observing the extreme ocean and weather conditions inside major hurricanes. These USVs will be an essential part of the Global Ocean Observing System, providing real-time data to improve prediction of rapid climate change and extreme ocean and weather events, and to reduce their harmful impacts.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Early Last Interglacial environmental changes recorded by speleothems from Katerloch (south‐east Austria) - Charlotte Honiat; Daniela Festi; Paul S. Wilcox; R. Lawrence Edwards; Hai Cheng; Christoph Spötl (Journal of Quaternary Science, 2022)
In the European Alps, the Last Interglacial (LIG, ~129–116 ka) has been primarily studied using pollen preserved in mires and lake sediments. These records document the vegetation succession across the LIG, but are poorly constrained chronologically. Here, we present a precisely dated stable isotope record for the early LIG (129.6 ± 0.4 to 125.0 ± 0.8 ka) based on two stalagmites from Katerloch, a cave located on the south‐eastern side of the Alps. The onset of the interglacial is marked by a sharp rise in the oxygen isotope values at 129.4 ± 0.4 ka, consistent within dating uncertainty with the timing of Termination II as recorded by other Alpine speleothems. Carbon isotope values show an equally prominent drop at Termination II and the establishment of a forest ecosystem. Although concentrations are low, pollen from these stalagmites provide insights into how the local vegetation changed across the first five millennia of the LIG. The spectra indicate a vegetation optimum recorded by the occurrence of warm‐demanding taxa typical of the Eemian mesocratic phase. By combining stable isotopes and pollen data, we propose an absolutely dated chronological framework for peri‐Alpine pollen successions from lacustrine sediments covering the first half of the LIG.

Temporal Baseline of Essesntial and Non-essential Elements Recorded in Baleen of Western Arctic Bowhead Whale (Balaena mysticetus) - Samantha L. Shore; Dimitrios G. Giarikos; Lawrence K. Duffy; Mickie R. Edwards; Amy C. Hirons (Bulletin of Environmental Contamination and Toxicology, 2022)
This study established the first baseline of changing elemental concentrations in bowhead whale baleen over time (1958–1999). From previously published stable isotope data, year, season (summer or winter), and location (Beaufort or Bering/Chukchi seas) were attributed to each sample. Thirteen elements (Al, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, V, Zn) in baleen from nine subsistence-harvested bowhead whales (n = 138) were detected. Al, Cu, and Fe were the highest concentrations while Cd and V were among the lowest. Our data supports absorption as the main route of exposure to environmental elements rather than biomagnification due to bowhead whales’ low trophic position. A linear mixed-effects model confirmed most elements’ concentrations increased with time, while location and sex were insignificant explanatory factors. These temporal fluctuations were most likely a product of environmental changes due to a warming climate and human activities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Speleothem‐based chronology and environmental context of deposits from the Mishin Kamik Cave, NW Bulgaria – A contribution to the archaeological study of the Late Pleistocene human occupation in the Balkans - Sophie Verheyden; Elena Marinova; Stefanka Ivanova; Christian Burlet; Hai Cheng; Lawrence R. Edwards; Thomas Goovaerts; Maria Gurova (Journal of Quaternary Science, 2021)
The Balkan Peninsula represents one of the most important human pathways into and out of Europe during the Pleistocene. Mishin Kamik cave, located in the karst region of Western Stara Planina, has a rich faunal content and shows promising features indicating a human occupation site with the discovery of potential bone artefacts and an intriguing accumulation of bear skulls and bones. Petrographic study and U‐series dating of a stalagmite and other calcite deposits in the cave provide an absolute chronological frame for the detrital infillings and their archaeological content and inform the environmental and climatic context of the cave evolution. Most detrital deposits in the cave were probably deposited before Marine Isotope Stage (MIS) 5 and the cave morphology and sedimentary deposits display current morphologies since ~135 ka. Consequently, the palaeontological and archaeological findings are older than ~135 ka. Calcite dated on and under the accumulation of bear skulls and bones suggests deposition during MIS 7. A first depositional contextualization of the bone accumulation does not allow us to discriminate between a natural or anthropogenic origin. The study emphasizes the added value of speleothem studies in archaeological sites and particularly in bringing a well‐constrained chronological and environmental framework.

Summer Monsoon Rainfall Variability in Central China over the Past 4700 Years and Its Possible Link to Solar Activity - Jingwei Zhang; Kan Zhao; Xinggong Kong; Yongjin Wang; Xianfang Wang; Shushuang Liu; Zhenjun Wang; Hai Cheng; R. Lawrence Edwards (Journal of Meteorological Research, 2021)

Exploring the Pacific Arctic Seasonal Ice Zone With Saildrone USVs - Andrew M. Chiodi; Chidong Zhang; Edward D. Cokelet; Qiong Yang; Calvin W. Mordy; Chelle L. Gentemann; Jessica N. Cross; Noah Lawrence-Slavas; Christian Meinig; Michael Steele; Don E. Harrison; Phyllis J. Stabeno; et al. (Frontiers in Marine Science, 2021)
More high-quality, in situ observations of essential marine variables are needed over the seasonal ice zone to better understand Arctic (or Antarctic) weather, climate, and ecosystems. To better assess the potential for arrays of uncrewed surface vehicles (USVs) to provide such observations, five wind-driven and solar-powered saildrones were sailed into the Chukchi and Beaufort Seas following the 2019 seasonal retreat of sea ice. They were equipped to observe the surface oceanic and atmospheric variables required to estimate air-sea fluxes of heat, momentum and carbon dioxide. Some of these variables were made available to weather forecast centers in real time. Our objective here is to analyze the effectiveness of existing remote ice navigation products and highlight the challenges and opportunities for improving remote ice navigation strategies with USVs. We examine the sources of navigational sea-ice distribution information based on post-mission tabulation of the sea-ice conditions encountered by the vehicles. The satellite-based ice-concentration analyses consulted during the mission exhibited large disagreements when the sea ice was retreating fastest (e.g., the 10% concentration contours differed between analyses by up to ∼175 km). Attempts to use saildrone observations to detect the ice edge revealed that in situ temperature and salinity measurements varied sufficiently in ice bands and open water that it is difficult to use these variables alone as a reliable ice-edge indicator. Devising robust strategies for remote ice zone navigation may depend on developing the capability to recognize sea ice and initiate navigational maneuvers with cameras and processing capability onboard the vehicles.

Autonomous vehicle surveys indicate that flow reversals retain juvenile fishes in a highly advective high‐latitude ecosystem - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Rebecca Woodgate; Calvin W. Mordy; Franz Mueter; Edward Cokelet; Noah Lawrence‐Slavas; Heather Tabisola (Limnology and Oceanography, 2021)
Summer surveys of the Chukchi Sea indicate that high densities of age‐0 gadid fishes, historically Arctic cod ( Boreogadus saida ) but recently also walleye pollock ( Gadus chalcogrammus ), dominate the pelagic fish community. Adults are comparatively scarce, suggesting that either overwinter survivorship of age‐0 gadids is low, or that they emigrate to other areas of the Pacific Arctic. To examine population movement, we conducted repeat acoustic surveys with saildrone autonomous surface vehicles equipped with echosounders throughout summer 2018. The saildrones' range and endurance enabled two large‐scale surveys of the U.S. Chukchi shelf. Acoustic backscatter, a proxy for fish density, was highest in regions with sea surface temperatures of 6–8°C, and lowest in areas influenced by recent ice melt. A subarea of the central Chukchi was surveyed a total of four times; backscatter in this subarea increased by > 85% from late‐July to mid‐September. As summer progressed, fish developed more extensive diel vertical migrations and backscatter from individuals doubled. Both changes suggest increases in backscatter were driven primarily by increasing body size. Particle tracking simulations indicated age‐0 gadids were likely retained over the Chukchi shelf by extended periods of wind‐driven southward flow during the survey period before strong northward flow in late fall transported them to the north. These findings suggest that in summer 2018, age‐0 gadids were advected northward to the Chukchi shelf from the northern Bering Sea, where they were retained during a period of growth until late fall before being advected farther north toward the Chukchi and Beaufort shelf breaks.

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

From cave geomorphology to Palaeolithic human behaviour: speleogenesis, palaeoenvironmental changes and archaeological insight in the Atxurra‐Armiña cave (northern Iberian Peninsula) - Martin Arriolabengoa; Inaki Intxaurbe; Mª Ángeles Medina‐Alcaide; Olivia Rivero; Joseba Rios‐Garaizar; Inaki LÍbano; Peru Bilbao; Arantza Aranburu; Hai Cheng; Richard Lawrence Edwards; Diego Garate (Journal of Quaternary Science, 2020)
A detailed geomorphological study was performed in the Atxurra‐Armiña cave system (northern Iberian Peninsula) to decode landscape evolution, palaeoenvironmental changes and human use of a cave within an Inner Archaeological Context. The results show an average incision rate of the river of –1 for at least the last 419 ka, with interruptions due to sedimentary inputs. Moreover, allostratigraphic units comprising fluviokarstic deposits at the base and flowstone formation at the top have been shown to be climatically controlled, formed either during glacial–interglacial cycles or during interstadial cycles. Finally, when the cave was used by humans in the Late Magdalenian, the lower entrance was closed, and they must therefore have entered the cave through the upper entrance. To reach the sectors selected to decorate the panels, they probably travelled from the upper cave level, as the current crawlway was wider than today, according to our U/Th dating. Once these visitors reached the panels, the floor in the main gallery would have been around 15 cm lower than at present. However, the morphology of the conduit was similar; this has significant implications for understanding and interpreting the human use of the cave during the Palaeolithic.

Taxonomy of prokaryotic viruses: 2018-2019 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Matthew B. Sullivan; Petar Knezevic; Leonardo J. van Zyl; B. L. Sarkar; Bas E. Dutilh; Poliane Alfenas-Zerbini; Małgorzata Łobocka; Yigang Tong; James Rodney Brister; Andrea I. Moreno Switt; Jochen Klumpp; et al. (Archives of Virology, 2020)

Decrease in 230 Th in the Amundsen Basin since 2007: far-field effect of increased scavenging on the shelf? - Ole Valk; Michiel M. Rutgers van der Loeff; Walter Geibert; Sandra Gdaniec; S. Bradley Moran; Kate Lepore; Robert Lawrence Edwards; Yanbin Lu; Viena Puigcorbé; Nuria Casacuberta; Ronja Paffrath; William Smethie; et al. (Ocean Science, 2020)
This study provides dissolved and particulate 230Th and 232Th results as well as particulate 234Th data collected during expeditions to the central Arctic Ocean (GEOTRACES, an international project to identify processes and quantify fluxes that control the distributions of trace elements; sections GN04 and GIPY11). Constructing a time series of dissolved 230Th from 1991 to 2015 enables the identification of processes that control the temporal development of 230Th distributions in the Amundsen Basin. After 2007, 230Th concentrations decreased significantly over the entire water column, particularly between 300 and 1500 m. This decrease is accompanied by a circulation change, evidenced by a concomitant increase in salinity. A potentially increased inflow of water of Atlantic origin with low dissolved 230Th concentrations leads to the observed depletion in dissolved 230Th in the central Arctic. Because atmospherically derived tracers (chlorofluorocarbon (CFC), sulfur hexafluoride (SF6)) do not reveal an increase in ventilation rate, it is suggested that these interior waters have undergone enhanced scavenging of Th during transit from Fram Strait and the Barents Sea to the central Amundsen Basin. The 230Th depletion propagates downward in the water column by settling particles and reversible scavenging.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Public–Private Partnerships to Advance Regional Ocean-Observing Capabilities: A Saildrone and NOAA-PMEL Case Study and Future Considerations to Expand to Global Scale Observing - Christian Meinig; Eugene F. Burger; Nora Cohen; Edward D. Cokelet; Meghan F. Cronin; Jessica N. Cross; Sebastien de Halleux; Richard Jenkins; Andrew T. Jessup; Calvin W. Mordy; Noah Lawrence-Slavas; Adrienne J. Sutton; et al. (Frontiers in Marine Science, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Towards an African Light Source - Simon H. Connell; Sekazi K. Mtingwa; Tabbetha Dobbins; Nkem Khumbah; Brian Masara; Edward P. Mitchell; Lawrence Norris; Prosper Ngabonziza; Tshepo Ntsoane; Herman Winick (Biophysical Reviews, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Reconstructing the western boundary variability of the Western Pacific Subtropical High over the past 200 years via Chinese cave oxygen isotope records - Jingyao Zhao; Hai Cheng; Yan Yang; Liangcheng Tan; Christoph Spötl; Youfeng Ning; Haiwei Zhang; Xing Cheng; Zhe Sun; Xianglei Li; Hanying Li; Wen Liu; et al. (Climate Dynamics, 2019)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Breast Cancer Patients’ Preferences for Adjuvant Radiotherapy Post Lumpectomy: Whole Breast Irradiation vs. Partial Breast Irradiation—Single Institutional Study - Katija Bonin; Merrylee McGuffin; Roseanna Presutti; Tamara Harth; Aruz Mesci; Deb Feldman-Stewart; Edward Chow; Lisa Di Prospero; Danny Vesprini; Eileen Rakovitch; Justin Lee; Lawrence Paszat; et al. (Journal of Cancer Education, 2018)

Avoided economic impacts of climate change on agriculture: integrating a land surface model (CLM) with a global economic model (iPETS) - Xiaolin Ren; Matthias Weitzel; Brian C. O’Neill; Peter Lawrence; Prasanth Meiyappan; Samuel Levis; Edward J. Balistreri; Michael Dalton (Climatic Change, 2018)

Advances in Ecosystem Research: Saildrone Surveys of Oceanography, Fish, and Marine Mammals in the Bering Sea - Calvin Mordy; Edward Cokelet; Alex De Robertis; Richard Jenkins; Carey Kuhn; Noah Lawrence-Slavas; Catherine Berchok; Jessica Crance; Jeremy Sterling; Jessica Cross; Phyllis Stabeno; Christian Meinig; et al. (Oceanography, 2017)

Decreasing monsoon precipitation in southwest China during the last 240 years associated with the warming of tropical ocean - Liangcheng Tan; Yanjun Cai; Zhisheng An; Hai Cheng; Chuan-Chou Shen; Yongli Gao; R. Lawrence Edwards (Climate Dynamics, 2017)

Variability and anatomical specificity of the orbitofrontothalamic fibers of passage in the ventral capsule/ventral striatum (VC/VS): precision care for patient-specific tractography-guided targeting of deep brain stimulation (DBS) in obsessive compulsive disorder (OCD) - Nikolaos Makris; Yogesh Rathi; Palig Mouradian; Giorgio Bonmassar; George Papadimitriou; Wingkwai I. Ing; Edward H. Yeterian; Marek Kubicki; Emad N. Eskandar; Lawrence L. Wald; Qiuyun Fan; Aapo Nummenmaa; et al. (Brain Imaging and Behavior, 2016)

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Widespread Chemical Detoxification of Alkaloid Venom by Formicine Ants - Edward G. LeBrun; Peter J. Diebold; Matthew R. Orr; Lawrence E. Gilbert (Journal of Chemical Ecology, 2015)

Neuroendocrine and sympathetic responses to an orexin receptor antagonist, SB-649868, and Alprazolam following insulin-induced hypoglycemia in humans - Ameera X. Patel; Sam R. Miller; Pradeep J. Nathan; Ponmani Kanakaraj; Antonella Napolitano; Philip Lawrence; Annelize Koch; Edward T. Bullmore (Psychopharmacology, 2014)

Trophic dynamics of U, Ni, Hg and other contaminants of potential concern on the Department of Energy’s Savannah River Site - Paul G. Edwards; Karen F. Gaines; A. Lawrence Bryan; James M. Novak; Susan A. Blas (Environmental Monitoring and Assessment, 2014)

Do mutator mutations fuel tumorigenesis? - Edward J. Fox; Marc J. Prindle; Lawrence A. Loeb (Cancer and Metastasis Reviews, 2013)

Imported crazy ant displaces imported fire ant, reduces and homogenizes grassland ant and arthropod assemblages - Edward G. LeBrun; John Abbott; Lawrence E. Gilbert (Biological Invasions, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Carbon outcomes of major land‐cover transitions in SE Asia: great uncertainties and REDD + policy implications - Alan D. Ziegler; Jacob Phelps; Jia QI Yuen; Edward L. Webb; Deborah Lawrence; Jeff M. Fox; Thilde B. Bruun; Stephen J. Leisz; Casey M. Ryan; Wolfram Dressler; Ole Mertz; Unai Pascual; et al. (Global Change Biology, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD + debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.

The Global Paleomonsoon as seen through speleothem records from Asia and the Americas - Hai Cheng; Ashish Sinha; Xianfeng Wang; Francisco W. Cruz; R. Lawrence Edwards (Climate Dynamics, 2012)

Introduction of the fire ant decapitating fly Pseudacteon obtusus in the United States: factors influencing establishment in Texas - Robert M. Plowes; Edward G. LeBrun; Lawrence E. Gilbert (BioControl, 2011)

Effects of sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor desensitizing agent on alcohol and nicotine self-administration in selectively bred alcohol-preferring (P) rats - Amir H. Rezvani; Susan Slade; Cori Wells; Ann Petro; Lawrence Lumeng; Ting-Kai Li; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Jed E. Rose; Kenneth J. Kellar; et al. (Psychopharmacology, 2010)

Mitochondrial mutagenesis induced by tumor-specific radiation bystander effects - Sheeona Gorman; Edward Fox; Diarmuid O’Donoghue; Kieran Sheahan; John Hyland; Hugh Mulcahy; Lawrence A. Loeb; Jacintha O’Sullivan (Journal of Molecular Medicine, 2010)

Precise dating of abrupt shifts in the Asian Monsoon during the last deglaciation based on stalagmite data from Yamen Cave, Guizhou Province, China - Yan Yang; DaoXian Yuan; Hai Cheng; MeiLiang Zhang; JiaMing Qin; YuShi Lin; XiaoYan Zhu; R. Lawrence Edwards (Science China Earth Sciences, 2010)

Estuarine Ecosystem Response Captured Using a Synoptic Climatology - David G. Kimmel; W. David Miller; Lawrence W. Harding; Edward D. Houde; Michael R. Roman (Estuaries and Coasts, 2009)

Dynamic expansion in recently introduced populations of fire ant parasitoids (Diptera: Phoridae) - Edward G. LeBrun; Robert M. Plowes; Lawrence E. Gilbert (Biological Invasions, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Wind strength and biological productivity in upwelling systems: an idealized study - Louis W. Botsford; Cathryn A. Lawrence; Edward P. Dever; Alan Hastings; John Largier (Fisheries Oceanography, 2003)
Biological production in wind‐driven coastal upwelling systems is of global importance. To understand better how wind speed and shelf width affect productivity, we formulated a simple model of cross‐shelf transport that included the dynamics of one potential mechanism: increasing nutrients with increasing winds, with possible loss of productivity due to off‐shelf Ekman transport. We used this model to determine how shelf productivity would depend on wind speed and shelf width using several ecosystem (Nutrient–Phytoplankton–Zooplankton, NPZ) models that reflect different trophic pathways and differences in model stability. For constant wind speeds, shelf productivity for all of the NPZ models declined beyond a certain wind speed. The shelf transit time beyond which productivity declines can be determined graphically from the time course of cumulative production in the NPZ model. Shelf width and latitude then determine the corresponding wind speed. The predicted points of decline in productivity with wind‐speed were consistent with data from local observations of higher trophic levels on the central California coast. Only shelf productivity of the NPZ model reflecting new production was dome‐shaped. Shelf productivity of models of regenerated production remained constant with wind speed at low winds. Artificial instability in NPZ models can lead to an inaccurate dependence of productivity on wind. Our model of coastal upwelling, which represents production as cross‐shelf transport of parcels containing developing NPZ models, exhibits a different dependence on wind forcing than previous models that represented upwelling production as a fully mixed shelf. The relative degree of mixing versus transport in upwelling systems is a critical factor underlying the dependence of productivity on wind.

Phylogeny of Marine Bacillus Isolates from the Gulf of Mexico - Janet L. Siefert; Maia Larios-Sanz; Lawrence K. Nakamura; Ralph A. Slepecky; John H. Paul; Edward R. B. Moore; George E. Fox; Peter Jurtshuk, Jr. (Current Microbiology, 2000)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Strain measurements in cultured vascular smooth muscle cells subjected to mechanical deformation - Kenneth A. Barbee; Edward J. Macarak; Lawrence E. Thibault (Annals of Biomedical Engineering, 1994)

Toxicity of five shale oils to fish and aquatic invertebrates - Daniel F. Woodward; Edward E. Little; Lawrence M. Smith (Archives of Environmental Contamination and Toxicology, 1987)

Altered purine and pyrimidine metabolism in erythrocytes with purine nucleoside phosphorylase deficiency - Irving H. Fox; Jan Kaminska; N. Lawrence Edwards; Erwin Gelfand; Kenneth C. Rich; William N. Arnold (Biochemical Genetics, 1980)